Reduced expansion of CD94/NKG2C+ NK cells in chronic lymphocytic leukemia and CLL‐like monoclonal B‐cell lymphocytosis is not related to increased human cytomegalovirus seronegativity or NKG2C deletions. (22nd February 2021) - Puiggros, Anna; Blanco, Gonzalo; Muntasell, Aura; Rodríguez‐Rivera, María; Nonell, Lara; Altadill, Mireia; Puigdecanet, Eulàlia; Arnal, Magdalena; Calvo, Xavier; Gimeno, Eva; Abella, Eugènia; Abrisqueta, Pau; et al.
Abstract: Introduction: Dysregulated NK cell‐mediated immune responses contribute to tumor evasion in chronic lymphocytic leukemia (CLL), although the NK cell compartment in CLL‐like monoclonal B‐cell lymphocytosis (MBL) is poorly understood. In healthy individuals, human cytomegalovirus (HCMV) induces the expansion of NK cells expressing high levels of CD94/NKG2C NK cell receptor (NKR) specific for HLA‐E. Methods: We analyzed the expression of NKG2A, NKG2C, ILT2, KIR, CD161, and CD57 in 24 MBL and 37 CLL. NKG2C was genotyped in these patients and in 81 additional MBL/CLL, while NKG2C gene expression was assessed in 26 cases. In 8 CLL patients with increased lymphocytosis (≥20 × 10 9 /L), tumor HLA‐E and HLA‐G expression was evaluated. Results: NKR distribution did not significantly differ between MBL and CLL patients, although they exhibited reduced NKG2C + NK cells compared with a non‐CLL group (4.6% vs 12.2%, P  = .012). HCMV + patients showed increased percentages of NKG2C + NK cells compared with HCMV − (7.3% vs 2.9%, P  = .176). Frequencies of NKG2C deletions in MBL/CLL were similar to those of the general population. Low/undetectable NKG2C expression was found among NKG2C +/− (45%) and NKG2C +/+ (12%) patients. CLL cases with increased lymphocytosis displayed especially reduced NKG2C expression (1.8% vs 8.1%, P  = .029) and tumor cells with high HLA‐E (>98%) and variable HLA‐G expression (12.4%, range: 0.5‐56.4). CLL patients with low NKG2C expression (<7%) showed shorter time to first treatment ( P  = .037). Conclusion: Reduced percentages of CD94/NKG2C + NK cells were observed in CLL and MBL patients independently of HCMV serostatus and NKG2C zygosity, particularly in CLL patients with increased lymphocytosis, which could potentially be related to the exposure to tumor cells.